Adventure tourism and schistosomiasis: serology and clinical findings in a group of Danish students after white-water rafting in Uganda. (2nd February 2018) - Röser, Dennis; Bjerrum, Stephanie; Helleberg, Marie; Nielsen, Henrik Vedel; David, Kim Peter; Thybo, Søren; Stensvold, Christen Rune
Abstract : Introduction. Diagnosis of schistosomiasis in travellers is a clinical challenge, since cases may present with no symptoms or a few non-specific symptoms. Here, we report on the laboratory and clinical findings in Danish travellers exposed to Schistosoma -infested water during white-water rafting on the Ugandan part of the upper Nile River in July 2009. Case presentation. Forty travellers were offered screening for Schistosoma -specific antibodies. Serological tests were performed 6–65 weeks after exposure. A self-reporting questionnaire was used to collect information on travel activity and health history, fresh water exposure, and symptoms. Seropositive cases were referred to hospitals where clinical and biochemical data were collected. Schistosoma -specific antibodies were detected in 13/35 (37 %) exposed participants, with 4/13 (31 %) seroconverting later than 2 months following exposure. Four of thirteen (31 %) cases reported ≥3 symptoms compatible with schistosomiasis, with a mean onset of 41 days following exposure. No Schistosoma eggs were detected in stool or urine in any of the cases. Peripheral eosinophilia (>0.45×10 9 cells l −1 ) was seen in 4/13 cases, while IgE levels were normal in all cases. Conclusion. Schistosomiasis in travellers is not necessarily associated with specific signs or symptoms, eosinophilia, raised IgE levels, or detection of eggs. The only prognostic factor for infection was exposure to freshwater in a Schistosoma -endemic area. Seroconversion may occur later than 2 months after exposure and therefore – in the absence of other diagnostic evidence – serology testing should be performed up to at least 2–3 months following exposure to be able to rule out schistosomiasis.